Implementasi Kebijakan Netralitas TNI Dalam Berpolitik Sebagai Unsur Lembaga Pertahanan Di Pusdiklatkopassus - Indi Ramadantica (Fisip UIN Sunan Gunung Djati Bandung, 2024)
The implementation of the political neutrality policy of the Indonesian National Armed Forces (TNI) is crucial for maintaining TNI's integrity and professionalism in Indonesia's dynamic political landscape. This article examines the implementation of neutrality policy at the Special Forces Command Training and Education Center (Pusdiklat Kopassus), focusing on political involvement, political rights of TNI members, and the effectiveness of neutrality policy. The study adopts a qualitative approach with a case study methodology, gathering data through interviews, observations, and document analysis. Findings reveal that Pusdiklat Kopassus has integrated neutrality training into its curriculum, coupled with rigorous internal oversight to ensure policy compliance. However, limitations in the political rights of TNI members may affect neutrality implementation. In conclusion, this article recommends strategies to strengthen neutrality policy to safeguard TNI's professionalism and integrity amidst Indonesia's dynamic political context.